Motion detection with NMR markers using real‐time field tracking in the laboratory frame. Issue 1 (16th December 2019) - Aranovitch, Alexander; Haeberlin, Maximilian; Gross, Simon; Dietrich, Benjamin E.; Reber, Jonas; Schmid, Thomas; Pruessmann, Klaas P.
Abstract : Purpose: To enhance the utility of motion detection with nuclear magnetic resonance (NMR) markers by removing the need for sequence‐dependent calibration. Methods: Two sets of NMR markers are used for simultaneous observation of magnetic field dynamics during imaging procedures. A set of stationary markers at known positions in the laboratory frame serves to determine the field evolution in that frame. Concurrent recording from a set of head‐mounted markers then permits calculating their lab‐frame positions and derived rigid‐body motion parameters. The precision and accuracy of this approach are evaluated relative to current calibration‐based solutions. Use for prospective motion correction is then demonstrated in high‐resolution imaging of long scan duration. Results: Motion detection with real‐time field tracking overcomes the need for explicit calibration without compromising precision, which is assessed at 10 to 30 µm. Relative to full conventional calibration, it is found to offer superior robustness against thermal drift. Relative to more economical modes of calibration, it achieves substantially higher accuracy. Prospective motion correction based on real‐time field tracking resulted in consistently high image quality even when head motion exceeded the image resolution by one order of magnitude. Conclusion: Real‐time field tracking enables motion detection with NMR markers without calibration overhead and thus overcomes a key obstacle toward routine use. In addition, it renders this mode of motion tracking more robust against system imperfections.